Legal Writing. - Webley, Lisa (Taylor and Francis, 2013)
Legal Writing guides students comprehensively through this vital legal skill and addresses a range of assessment methods, from exam questions to final essays and problem answers. It considers how to deconstruct essay and problem questions and how to conduct and apply legal research to answer set questions. Lisa Webley explains how to reference others' work clearly and correctly, making this book a useful tool for students concerned about issues of plagiarism. It also focuses on how to develop and communicate legal arguments, with both good and bad examples of written work co.